Combined stent-retriever and aspiration intra-arterial thrombectomy performance for fragmentable blood clots: A proof-of-concept computational study. (November 2022) - Luraghi, Giulia; Bridio, Sara; Lissoni, Vittorio; Dubini, Gabriele; Dwivedi, Anushree; McCarthy, Ray; Fereidoonnezhad, Behrooz; McGarry, Patrick; Gijsen, Frank J.H.; Rodriguez Matas, Jose Felix; Migliavacca, Francesco
Abstract: Mechanical thrombectomy (MT) treatment of acute ischemic stroke (AIS) patients typically involves use of stent retrievers or aspiration catheters alone or in combination. For in silico trials of AIS patients, it is crucial to incorporate the possibility of thrombus fragmentation during the intervention. This study focuses on two aspects of the thrombectomy simulation: i) Thrombus fragmentation on the basis of a failure model calibrated with experimental tests on clot analogs; ii) the combined stent-retriever and aspiration catheter MT procedure is modeled by adding both the proximal balloon guide catheter and the distal access catheter. The adopted failure criterion is based on maximum principal stress threshold value. If elements of the thrombus exceed this criterion during the retrieval simulation, then they are deleted from the calculation. Comparison with in-vitro tests indicates that the simulation correctly reproduces the procedures predicting thrombus fragmentation in the case of red blood cells rich thrombi, whereas non-fragmentation is predicted for fibrin-rich thrombi. Modeling of balloon guide catheter prevents clot fragments' embolization to further distal territories during MT procedure.